Excitation of high-radial-order Laguerre–Gaussian modes in a solid-state laser using a lower-loss digitally controlled amplitude mask. (13th September 2017) - Bell, T; Hasnaoui, A; Ait-Ameur, K; Ngcobo, S
Abstract: In this paper we experimentally demonstrate selective excitation of high-radial-order Laguerre–Gaussian (LG p or LG p, 0 ) modes with radial order p = 1–4 and azimuthal order l = 0 using a diode-pump solid-state laser (DPSSL) that is digitally controlled by a spatial light modulator (SLM). We encoded an amplitude mask containing p -absorbing rings, of various incompleteness (segmented) on grey-scale computer-generated digital holograms, and displayed them on an SLM which acted as an end mirror of the diode-pumped solid-state digital laser. The various incomplete ( α ) p -absorbing rings were digitally encoded to match the zero-intensity nulls of the desired LG p mode. We show that the creation of LG p, for p = 1 to p = 4, only requires an incomplete circular p -absorbing ring that has a completeness of ≈37.5%, giving the DPSSL resonator a lower pump threshold power while maintaining the same laser characteristics (such as beam propagation properties).